State Planning Board West Bengal 1974-76 - Planning Commission (Planning Commission, 1976)
Planning is a frame embodying the policy-mix that would help in the expeditious realisation of our development goals and egalitarian objectives. It is not enough to have development, it is also essential to ensure that development takes place speedily and that it facilitates the establishment of a social order in which the ideals of economic growth, social justice and self-reliance arc realised and harmonised. As planning is essential for conditioning and directing our economic activities for achieving these goals there cannot be any plan holiday or any retreat from these cherished goals.
State Planning Board Government of West Bengal